Recommended for you - Silverman, Laura (Margaret K. McElderry Books, 2021)
Shoshanna Greenberg loves working at Once Upon, her favorite local bookstore. It's a welcome escape from her moms constantly fighting and her close-to-death car. When her boss at Once Upon announces a holiday bonus to the person who sells the most books, Shoshanna wants to win in order to have enough money to fix her car, but one person stands in her way: Jake Kaplan, the cute new hire who doesn't read. As the competition between Shoshanna and Jake heats up, the two grow closer and realize that they might have more in common than she originally thought.